2008
DOI: 10.3174/ajnr.a1040
|View full text |Cite
|
Sign up to set email alerts
|

Subtraction 3D CT Angiography with the Orbital Synchronized Helical Scan Technique for the Evaluation of Postoperative Cerebral Aneurysms Treated with Cobalt-Alloy Clips

Abstract: BACKGROUND AND PURPOSE:CT angiography (CTA) has been used for the evaluation of intracranial aneurysms and recently has been applied to assess postoperative aneurysms treated with titanium-alloy clips. We investigated the clinical usefulness of subtraction CTA by using the orbital synchronized helical scan technique (OSHST) for evaluating intracranial aneurysms surgically treated with cobalt-alloy clips.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 10 publications
0
15
0
1
Order By: Relevance
“…11,15,16 Dehdashti et al 16 demonstrated, in a series of 60 clipped aneurysms with 90% of the cases being treated with a single clip, a 100% sensitivity and specificity for detecting neck remnants and an 80% sensitivity with 100% specificity for evaluating vessel patency. Gerardin et al 19 examined a population with significantly more clips per aneurysm and found lower sensitivity and specificity values, concluding that MDCTA is a valuable examination for aneurysm remnants with a diameter of Ͼ2 mm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11,15,16 Dehdashti et al 16 demonstrated, in a series of 60 clipped aneurysms with 90% of the cases being treated with a single clip, a 100% sensitivity and specificity for detecting neck remnants and an 80% sensitivity with 100% specificity for evaluating vessel patency. Gerardin et al 19 examined a population with significantly more clips per aneurysm and found lower sensitivity and specificity values, concluding that MDCTA is a valuable examination for aneurysm remnants with a diameter of Ͼ2 mm.…”
Section: Discussionmentioning
confidence: 99%
“…11,15,16 Again, the size of the neck remnant or the number of the implanted clips can limit the sensitivity of MDCTA. 15,[17][18][19] A new noninvasive technique for the depiction of the intracranial vasculature is IV-ACT-also known as flat detector CT or C-arm conebeam CT after intravenous contrast agent application.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The subtraction was done using the entire imaging volume dataset of precontrast CT and postcontrast CT. Subtraction images were calculated to subtract the CT value of the pixel on preconrast CT from the pixel on postcontrast CT. If misregistration artifacts are observed, they are corrected manually based on visual assessment using the Volume Position Matching function (Toshiba Medical Systems), which is a manual method for correcting positional shift by adjusting the positions of the images in three dimensions, similar to the "pixelshift" function in DSA [24]. This technology has been employed in 16 and 64-detector row CT systems to perform subtraction in examinations of the central nervous system and peripheral arteries.…”
Section: Subtraction Methodsmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13] Therefore, detection of the residual or recurrent aneurysms after clipping is clinically significant. All the time, both computed tomographic angiography (CTA) and digital subtraction angiography (DSA) are deemed as valuable tools to detect cerebral aneurysms, whereas the residual or recurrent aneurysms after clipping is mainly evaluated by the use of DSA.…”
Section: Introductionmentioning
confidence: 99%